A case of high density abnormality in x-ray findings of mandible caused by leakage of root canal filling paste. Issue 3 (December 2017) - Kashiwamura, Haruko; Oka, Kyoko; Tuchihashi, Yoko; Yoshioka, Hanako; Kato, Mayumi; Baba, Atsuko; Kagawa, Toyohiro; Okamura, Kazuhiko; Ozaki, Masao
Abstract: Background: Calcium hydroxide paste is widely used for endodontic treatment as a root canal filling material. However, appropriate filling with that paste at the root apex is difficult because of the properties of the material and tooth root condition. Case report: Here, we report a 4-year clinical follow-up of leakage of calcium hydroxide paste into the mandible during endodontic treatment. The remaining material observed radiologically for 4 years. During that period, 2 adjacent permanent teeth, the first molar and premolar, erupted normally, while radiopaque findings in the mandible bone shown by panoramic x-ray imaging slowly decreased without signs of inflammation.